2009
DOI: 10.1097/bot.0b013e31819a6651
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of High-Energy Femoral Neck-Shaft Fractures

Abstract: This study found a similar rate of neck-shaft combinations (3.2%), a higher rate of open fractures, and increased incidence of associated injuries compared with the literature. Most importantly, our data indicate that even with a negative preoperative computed tomography scan, a femoral neck fracture can be present. A trend also indicated more missed femoral neck fractures with retrograde nailing, which may be attributed to less fluoroscopic imaging of the hip with this technique. Patients with femoral shaft f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…A recent meta-analysis showed strong evidence suggesting that reamed IM nails had a higher union rate than unreamed IM nails, again confirmed by our recent investigation [5]. Most recently, a multicenter retrospective review of 76 high-energy ipsilateral femoral neck and shaft fractures treated by a variety of surgeons with fixation determined by surgeon discretion found complications in patients treated with proximal cannulated screws and a retrograde IM nail [7]. In the group where the femoral neck fracture was identified early, 33 were treated with cannulated screws and 16 with a sliding hip screw with a secondary retrograde IM nail.…”
Section: Discussionmentioning
confidence: 55%
“…A recent meta-analysis showed strong evidence suggesting that reamed IM nails had a higher union rate than unreamed IM nails, again confirmed by our recent investigation [5]. Most recently, a multicenter retrospective review of 76 high-energy ipsilateral femoral neck and shaft fractures treated by a variety of surgeons with fixation determined by surgeon discretion found complications in patients treated with proximal cannulated screws and a retrograde IM nail [7]. In the group where the femoral neck fracture was identified early, 33 were treated with cannulated screws and 16 with a sliding hip screw with a secondary retrograde IM nail.…”
Section: Discussionmentioning
confidence: 55%
“…This value is greater than the reported mean in the literature, 5%, but within the reported range. 1,2,5,8,13,14,19 Our analysis also demonstrated that the rate of missed femoral neck fractures must be .38% for the routine use of reconstruction nailing in femur fractures to be cost effective. The reported rates of missed femoral neck fractures are from 19% to 55%, and some recent literature has shown that experienced trauma surgeons still miss 22% of these fractures.…”
Section: Discussionmentioning
confidence: 82%
“…The reported rates of missed femoral neck fractures are from 19% to 55%, and some recent literature has shown that experienced trauma surgeons still miss 22% of these fractures. 8 If the incremental costs of reconstruction nailing are ,$360 then the missed femoral neck fracture must be .22% for reconstruction nailing to be the preferred strategy (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations